2020
DOI: 10.1186/s40560-020-00466-z
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer as a biomarker for disease severity and mortality in COVID-19 patients: a case control study

Abstract: Background: Over 5,488,000 cases of coronavirus disease-19 (COVID-19) have been reported since December 2019. We aim to explore risk factors associated with mortality in COVID-19 patients and assess the use of D-dimer as a biomarker for disease severity and clinical outcome. Methods: We retrospectively analyzed the clinical, laboratory, and radiological characteristics of 248 consecutive cases of COVID-19 in Renmin Hospital of Wuhan University, Wuhan, China from January 28 to March 08, 2020. Univariable and mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
334
8
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(483 citation statements)
references
References 21 publications
44
334
8
18
Order By: Relevance
“…D-dimer is a by-product generated when plasmin degrades fibrin clots; it is a useful marker of thrombotic activity [ 21 ]. Because of its prognostic significance, it has become a useful laboratory marker to assess disease severity in hospitalized Covid-19 patients [ 7 , 10 , 22 ]. Although frequently used to assess venous thromboembolism, D-dimer is under investigation to determine its utility in assessing the need for anticoagulation in Covid-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D-dimer is a by-product generated when plasmin degrades fibrin clots; it is a useful marker of thrombotic activity [ 21 ]. Because of its prognostic significance, it has become a useful laboratory marker to assess disease severity in hospitalized Covid-19 patients [ 7 , 10 , 22 ]. Although frequently used to assess venous thromboembolism, D-dimer is under investigation to determine its utility in assessing the need for anticoagulation in Covid-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials are ongoing currently in the USA [ 14 ]. However, there is little data that has established an important threshold: a recent paper found that patients on heparin anticoagulation had improved mortality when the D-dimer was > 3.0 μg/mL [ 13 ]; other groups have found that D-dimer > 2.14 mg/L (equivalent to μg/mL) obtained on hospital admission was 88.2% sensitive and 71.3% specific in detecting in-hospital mortality [ 22 ]. Similar to these results, we find here that mortality is associated with higher peak D-dimer levels and that an optimal peak D-dimer level of > 2.48 μg/mL has a 95% sensitivity and 58% specificity for in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Severe cases are marked by progression into the lower airways and alveoli. Here, it manifests as an atypical form of acute respiratory distress syndrome (ARDS) characterized by good lung compliance measurements 7,8 , and elevated levels of coagulation markers such as D-dimers 9 , and pro-inflammatory markers in the blood 10 . Autopsy reports show numerous microvascular thrombi in the lungs of deceased patients together with evidence of the intracellular presence of the virus in vascular cells 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Markers of COVID-19 severity have been proposed. [5][6][7] MALDI-MS has been successfully implemented into the microbiology field building reference spectral libraries for rapid, sensitive and specific identification of bacterial and fungal species. 8 This approach is well established and accepted in many countries for routine diagnostics of yeast and bacterial infections.…”
Section: Introductionmentioning
confidence: 99%